2011
DOI: 10.9738/cc44.1
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Catheter-Guided Laser Ablation: A Novel Alternative for Branch Varicose Veins

Abstract: It is difficult to manage tributary varicose veins with endovenous laser ablation. Using the intravenous catheter-guided laser fiber to ablate the tributary varicose veins has been proposed. From April 2004 to December 2009, we randomly assigned 134 patients with 170 limbs for laser therapy, of which, 89 limbs in 74 patients were treated with laser ablation. The residual tortuous veins were abolished with the intravenous catheter-guided laser ablation (ICLA group), whereas residual varicose veins in 81 limbs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Many approaches have been used for the treatment of varicose veins [1][2][3][4] including ligation and stripping, foam sclerotherapy, radiofrequency, and laser therapy. Our previous studies 1,2 showed that laser therapy is better than trivex for tributary varicose veins, and laser therapy with catheter has its unique advantage in the treatment of tributary varicose veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches have been used for the treatment of varicose veins [1][2][3][4] including ligation and stripping, foam sclerotherapy, radiofrequency, and laser therapy. Our previous studies 1,2 showed that laser therapy is better than trivex for tributary varicose veins, and laser therapy with catheter has its unique advantage in the treatment of tributary varicose veins.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized with earlier return to work, less pain, and improved quality of life after endovenous laser ablation in comparison with open surgery. [1][2][3][4][5] However, like many other surgical procedures, some related side effects, such as burns and blister, during or after laser ablation can occur. A retained foreign body could be left accidentally in the treated leg, which may cause postoperative discomfort or pain.…”
mentioning
confidence: 99%
“…3 In this procedure, a catheter is inserted and positioned at 2 cm below the saphenofemoral or saphenopopliteal junction. Local anesthesia is used with perivenous tumescent technique to prevent neural damage and skin burn.…”
Section: Endovenous Thermoablationmentioning
confidence: 99%
“…However, like other surgeries, EVLA still can cause operative or postoperative complications, such as hematoma, infection, skin burn, bruising, and catheter stabbing by laser fiber, or the broken catheter can be left in the body. 3,12,13 Many clinical studies and randomized controlled trials of high quality compared EVLA and conventional surgical procedures and showed no differences in postoperative pain, recurrence rates, or returning to work or normal activity. 7,14 Clinical experience shows that the pain after laser ablation contributes to the skin contusion caused between skin and uneven bandages used after the procedure, blisters induced by skin burn, and endovenous thermal-induced thrombosis and thrombophlebitis 7 ; all of these problems can be prevented with careful manipulation during the procedure.…”
Section: Endovenous Thermoablationmentioning
confidence: 99%
See 1 more Smart Citation